From Here to There, Progenitor Cells and Stem Cells Are Everywhere in Lung Vascular Remodeling - Heise, Rebecca L.; Link, Patrick A.; Farkas, Laszlo (Frontiers in Pediatrics, 2016)
The field of stem cell biology, cell therapy and regenerative medicine has expanded almost exponentially in the last decade. Clinical trials are evaluating the potential therapeutic use of stem cells in many adult and pediatric lung diseases with vascular component, such as bronchopulmonary dysplasia (BPD), chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF) or pulmonary arterial hypertension (PAH). Extensive research activity is exploring lung resident and circulating progenitor cells and their contribution to vascular complications of chronic lung diseases, and researchers hope to use resident or circulating stem/progenitor cells to treat chronic lung diseases and their vascular complications. It is becoming more and more clear that progress in mechanobiology will help to understand the various influences of physical forces and extracellular matrix composition on the phenotype and features of the progenitor cells and stem cells. The current review provides an overview of current concepts in the field.